Relational model of public-private partnership in railway transport - N. F. Sirina; V. P. Pershin (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
The main task facing the state is the solution of publicly significant issues to achieve public interests. Moreover, not every country has the necessary resources, especially in an unstable economic situation. In this case, increasing the efficiency of natural monopolies in the conjuncture of the transport market becomes the most relevant direction in government activities.The article is devoted to the issues of public-private partnership in railway transport. First of all, projects with private capital that are being implemented should eliminate the limiting sections of the Russian railway network and ensure the development of large industrial regions by creating an extensive transport network, the formation of which is impossible without the participation of the state.To increase the attractiveness of public-private partnership projects, the authors, taking into account the foundations of human capital management, have considered aspects of the additional effect for partners, which are defined by the concept of “relational effect”. Positive dynamics of socially oriented indicators, unaccounted in the agreement of the parties, reflect the presence of benefits from joint activities and positive relational effect, while negative change — about its absence.Based on the studies performed, a mechanism for controlling operating costs based on an integral assessment has been proposed, which makes it possible to analyze the actual direct costs of partners and compare deviations from the established standards. This mechanism is used in the state vertically integrated procedure for centralized training of authorities in public-private partnership. The general algorithm of the relational model of interaction between investment parties is formalized, illustrated by the example of the implementation of a project for the construction of a railway transport infrastructure.Mathematical support for the process of considering information on the project and making a decision on concluding an agreement on public-private partnership was carried out in the program “Automated system for consolidation, selection and control of the implementation of innovative projects of concession forms of management in railway transport”. The results obtained are integrated into the software complex for innovative development of facilities and are tuned for transformation, effective use of the potential of partners, investors, performers and industry enterprises.